The effect of alkali treatment under various conditions on physical properties of kenaf fiber - Hashim, Mohd Yussni; Mohd Amin, Azriszul; Marwah, Omar Mohd Faizan; Othman, Mohd Hilmi; Mohamed Yunus, Mohd Radzi; Ng, Chuan Huat (IOP Publishing, 2017)
Alkali treatment was known as one commonly used treatment for natural fiber and obtained a good fiber matrix adhesion, thermal and mechanical properties of composite. This paper reports the effect of alkali treatment conditions on the physical properties of kenaf fiber such as density, weight loss, diameter, cross sectional and fiber morphology. In this study, kenaf fiber were treated under various conditions alkali concentration at 2, 6 and 10 (w/v%), immersion duration at 30, 240 and 480 minute and immersion temperature at 27, 60 and 100oC. The effects of alkali treatment on kenaf fiber physical properties under various conditions were explored. Alkali treatment conditions setting have an impact on kenaf bast fiber physical characteristics. In kenaf fiber density, it was found that a small increase of kenaf density value after alkali treatment compared to untreated kenaf fiber. When each of alkali treatment parameters increased, kenaf fiber density also increased slightly. Kenaf fiber weight loss also exhibit a similar pattern of small increment with the increase of treatment parameters. Additionally, kenaf fiber diameter and cross sectional area show a decline pattern after treated with alkali. Furthermore, this decline pattern was corresponding with the increasing level of alkali treatment parameters. The maximum of kenaf diameter reduction was recorded at high level of each alkali treatment parameters.